Keabsahan Keadaan Solven Debitor sebagai Dasar Pertimbangan dalam Perkara Kepailitan - Clarita Stefanie Panjaitan; R. Kartikasari; Artaji Artaji (Universitas Airlangga, 2022)
AbstractThis article will discuss the basic considerations of the judge in considering the debtor’s solvent condition as the reason for rejecting the bankruptcy case. This article also provides an explanation that the consideration of debtor solvent conditions as the implementation of the principle of balance in the examination of bankruptcy cases is an essential thing to resolve the problems that occur in the Bankruptcy Law in order to create legal certainty for the parties The research method used in this article is a normative legal research method that is descriptive analytical, with the application of a normative juridical approach, by observing secondary data legal materials, with data collection techniques through document studies, with library analysis. The results of the article indicate that Judges must apply the principle of balance by taking into account the debtor’s solvent condition in examining Bankruptcy cases in order to protect the interests of the parties and the interests of the business community.Keywords: Bankruptcy; Insolvency Test; Principle of Balance.AbstrakPenelitian ini akan membahas mengenai dasar pertimbangan hakim dalam mempertimbangkan mengenai keadaan solven Debitor sebagai alasan penolakan perkara Kepailitan. Penelitian ini juga memberikan penjelasan bahwa pertimbangan keadaan solven Debitor sebagai implementasi asas keseimbangan dalam pemeriksaan perkara kepailitan, merupakan suatu hal yang esensial guna menyelesaikan problematika yang terjadi dalam Undang-Undang Kepailitan demi mewujudkan kepastian hukum bagi para pihak. Metode penelitian yang digunakan dalam penelitian ini adalah metode penelitian hukum normatif yang bersifat deskriptif analitis, dengan penerapan metode pendekatan yuridis normatif, dengan melakukan pengamatan terhadap bahan-bahan hukum data sekunder, dengan teknik pengumpulan data melalui studi dokumen, dengan analisis kepustakaan. Hasil penelitian menunjukkan bahwa Hakim haruslah menerapkan asas keseimbangan dengan turut mempertimbangkan keadaan solven Debitor dalam memeriksa perkara Kepailitan guna melindungi kepentingan para pihak serta kepentingan masyarakat bisnis.Kata Kunci: Kepailitan; Insolvency Test; Prinsip Keseimbangan.